PENGARUH DOSIS PUPUK DAN VARIETAS PADI PADA LAHAN SAWAH BUKAAN BARU DI PULAU BANGKA - Muzammil Muzammil; Sigit Puspito; Dede Rusmawan; Sugito Sugito; Wahyu Wibawa (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2021)
The effect of fertilizer dosage and rice varieties on productivity of rice in the new open paddy fields in Bangka island. Agriculture is a main sector in economic development in supporting food security in the Province of Bangka Belitung Islands. Food production, especially rice in the Bangka Belitung Province, has only been able to meet 45% of the total demand for rice in this area and the rest still has to be supplied from other regions. Efforts to increase rice production, the government continues to open new paddy fields to increase rice production. In the last 5 years, the area of new open paddy fields is 16,993 ha, of which 9,416 ha (55.41%) are located in South Bangka Regency and the rest are scattered in other districts. This study aims to determine the effect of giving several doses of fertilizers and varieties on rice production in new open paddy fields. The study design used a randomized block design with 2 factors, namely: The first factor was a fertilizer dose with 3 levels of treatment: a) Dose of fertilizer based on Katam / PUTS; b) The dosage of fertilizer based on recommendations from research institutes / universities / R&D; and c) Fertilizer dosage based on laboratory soil analysis results. The second factor was rice varieties with 3 treatment levels: a) Inpari 30 (V1); b) Inpara 2 (V2); and c) Local varieties of Beams (V3). The results of the study showed that the fertilizer dose treatment based on the analysis of the chemical properties of the soil and the Inpara 2 variety showed the highest production yield (5.02 t/ha) compared to other treatments. The Inpara 2 variety which is more adaptive to newly opened paddy fields with fertilizer application based on the results of the chemical analysis is recommended to increase the production. Keywords: fertilizer dosage, variety, paddy, new open paddy fieldsABSTRAK  Pertanian menjadi sektor andalan pembangunan ekonomi dalam mendukung ketahanan pangan di Provinsi Kepulauan Bangka Belitung. Produksi pangan khususnya beras di Provinsi Kepulauan Bangka Belitung hingga saat ini baru dapat mencukupi 45% dari total kebutuhan beras di daerah ini dan sisanya masih harus disuplay dari daerah lainnya. Salah satu upaya pemerintah untuk terus meningkatkan produksi beras adalah dengan melakukan pembukaan sawah baru. Pada kurun waktu 5 tahun terakhir luas sawah bukaan baru seluas 16.993 ha, dimana luas lahan tersebut 9.416 ha (55,41%) terdapat di Kabupaten Bangka Selatan dan sisanya tersebar di Kabupaten lainnya. Pengkajian ini bertujuan untuk mengetahui pengaruh pemberian beberapa dosis pupuk dan varietas  terhadap produksi padi pada lahan sawah bukaan baru di Pulau Bangka. Rancangan pengkajian menggunakan rancangan acak kelompok dengan 2 faktor yaitu: Faktor pertama berupa dosis pupuk dengan 3 taraf perlakuan: a) Dosis pupuk berdasarkan Katam/PUTS; b) Dosis pupuk berdasarkan rekomendasi dari lembaga penelitian/Universitas/Litbang; dan c) Dosis pupuk berdasarkan hasil analisis tanah laboratorium. Faktor kedua berupa varietas padi dengan 3 taraf perlakuan: a) Varietas Inpari 30 (V1); b) Varietas Inpara 2 (V2); dan c) Varietas lokal Balok (V3). Dari hasil pengkajian menunjukan bahwa perlakuan dosis pupuk berdasarkan hasil analisis sifat kimia tanah dan varietas Inpara 2 menunjukkan hasil produksi paling tinggi (5,02 t/ha) dibandingkan perlakuan lainnya.Varietas Inpara 2 yang lebih adaptif pada sawah bukaan baru dengan pemberian pupuk berdasarkan hasil analisis sifat kimia tanam direkomendasikan untuk peningkatan produksi. Kata kunci: dosis, varietas, padi, sawah bukaan baru